A adaptação de bebês na creche: um estudo de caso - Paula, Mariana Godoy de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This study aimed to answer the question: How does the process of school adaptation of children when we insert them in a daycare center? The overall aim was not only to know and to analyze the process of school adaptation of beginning children in access to a daycare center, in a private institution in Bauru, São Paulo but also to reflect on the importance of this process for children who are starting their school life. Furthermore, we reflect on about how the reception should occur, valuing a more rapid and calm adaptation, and considering the feelings of the parents, for leaving their children in an unknown environment. During the development of the study, we presented the history of daycare centers in Brazil and the changes occurred over the years, until the current context. The history of these institutions is a remarkable social achievement; starting from an assistance perspective until it reaches its legalization as a right of the child to the Childhood. Furthermore, it became a duty of the State, and integrating the daycare center to the first stage of basic education, as foreseen in the Federal Constitution of 1988 and the 1996 National Education Guidelines and Bases Act. We analyzed this adaptation process from a theoretical-methodological perspective, based on a case study that followed the insertion of ten children in a daycare center. This was recorded based on observations and interviews with a principal, a teacher, and three parents/guardians. We observed through the experiences and the data collected that this process is a complex moment for both, the children and the families, and for the educators. For this reason should be a well-planned, a structured reception process, involving care and affection, in order to reduce the possible suffering, making the stage calmer and less frightening for the child.

Este Trabalho de Conclusão de Curso buscou responder a pergunta: Como acontece o processo de adaptação escolar de crianças quando são inseridas na creche? Teve como objetivo geral conhecer e analisar o processo de adaptação escolar de crianças iniciantes no acesso à creche, em uma instituição particular no interior do Estado de São Paulo, assim como refletir sobre a importância desse processo para as crianças que estão iniciando sua vida escolar e também como deve ocorrer o acolhimento, valorizando uma adaptação mais rápida e tranquila, levando em conta os sentimentos dos pais, por estarem deixando seus filhos em um ambiente desconhecido. Durante o desenvolvimento do estudo foi apresentada a história das creches no Brasil e as mudanças que sofreram ao passar dos anos, até chegar no contexto atual. O histórico dessas instituições destaca-se como uma conquista social, partindo do cunho assistencialista até chegar à sua legalização como um direito da criança à Infância e dever do Estado, integrando a creche à primeira etapa da educação básica, conforme previsto na Constituição Federal de 1988 e na Lei de Diretrizes e Bases da Educação Nacional de 1996. Foi adotada uma perspectiva teórico-metodológico para analisar esse processo de adaptação, baseado em um estudo de caso que acompanhou a inserção de dez crianças em uma creche. Registrou-se a situação a partir de observações e entrevistas com a diretora, professora e três pais/responsáveis. Notou-se, por meio das experiências e dados coletados que esse processo é um momento complexo tanto para as crianças e os familiares quanto para os educadores e, por esse motivo, deve ser um processo de acolhimento, bem planejado, estruturado, envolvendo carinho e afeto, a fim de amenizar o possível sofrimento vivido, tornando uma etapa mais tranquila e menos assustadora para a criança.
Keywords: Educação de crianças; Creches; Adaptação escolar; Família; Aconselhamento familiar; Education